PENGARUH LAMA PEMANGGANGAN DALAM OVEN TERHADAP pH DAN ORGANOLEPTIK STEAK DAGING SAPI - Rita Purwasih; Hazna Azzahra (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Steak is one of the processed meat and physical quality associated with the cooking process, the physical quality in question is texture, pH, and organoleptic.The purpose of this research is to know the effect of roasting in an oven on pH and organoleptic steak of beef that is flavor, aroma, texture, appearance and favorite level.The experimental design used in this study was completely Randomized Design (RAL), with the difference in the duration of roasting time of P1 for 3 minutes (rare); P2 time of overview 5 min (medium rare); P3 is 7 minutes (medium well) and P4 time of curing time is 10 minutes (well done) at 2000C. Parameters measured were pH, an organoleptic test which included taste, aroma, texture, appearance and favorite level with 45 semi-media panelists. The result of treatment of P1, P2, P3 and P4 on average pH of beef before and after roasting did not change, whereas for panelist organoleptic test most liked P4 with the mean of 4,02; aroma 3,98; texture 4.07; 3.93 appearances; and preferred level of 4.09. This research is long roasting using oven does not change the pH steak beef. In general, panelists have a higher assessment on P4 that is viewed from the taste, aroma, texture, appearance, and level of fondness.